STORY-TELLING – A CONSTRUCTIVIST TOOL IN SCIENCE TEACHING - Tandon, Tanu (SCHOOL SCIENCE, 2011)
Constructivism asserts that knowledge is actively constructed by the learner through interaction with the world and social negotiation, learner explores the world and transforms his understanding of the world. Story-telling, is also an integral part of our lives, in understanding and communicating with the world. Science, on the other hand, is a subject which rests upon inductive reasoning and analytical thinking, and also requires social negotiation and classroom is the social unit where knowledge is constructed. This paper discusses how story-telling can be used as a constructivist tool in teaching of science.